Bangkok urban census of aquatic invertebrate fauna by an integrative taxonomic approach: the case of Suan Luang Rama IX Park and its freshwater sponges (Spongillida: Spongillidae) - Ruengsawang, Nisit; Sangpradub, Narumon; Cubeddu, Tiziana; Erpenbeck, Dirk; Wörheide, Gert; Pronzato, Roberto; Manconi, Renata (Zootaxa, 2025)
Faunistic investigations on freshwater bodies of the Bangkok Metropolitan Area resulted in the discovery of a freshwater sponge population fragmented in small lentic microhabitats at the Suan Luang Rama IX Park. Sponges living in the lotus and waterlily garden and tropical greenhouse were photographed in situ, and some representative, small samples were collected and stored at the Division of Biology (Porifera Collection), Rajamangala University of Technology Krungthep, Bangkok. The taxonomic integrative analyses focused on diagnostic morphotraits, barcoding, and biogeography. The sponge population was ascribed to Radiospongilla cf. cerebellata (Porifera: Demospongiae: Spongillida: Spongillidae) and is a new record for the Bangkok area and the entire Thai inland water. Comparative integrative analyses vs spongillid taxa worldwide resulted in the discovery of new gemmular morphotraits for the genus. Although the Thai Radiospongilla cf. cerebellata diverges from the Indian type of Radiospongilla cerebellata at the level of gemmular theca architecture, molecular analyses highlighted the matching of the former with the Radiospongilla cluster. A possible allochthonous origin of the Bangkok Radiospongillas population is hypothesised. This investigation on botanical gardens aquatic fauna and a review of appropriate literature highlights that sponges are able to inhabit very confined and fragmented, shallow water bodies, i.e., scattered terracotta pots, plastic containers, and small ponds with aquatic plants also in megalopolis gardens.